Standardized uptake value (SUV) measurement of normal vertebrae and pelvis using SPECT/CT with 99mTc methylene diphosphonate (99mTc-MDP) - Wei, Tee Li (Universiti Sains Malaysia, 2025)
In Single Photon Emission Computed Tomography/Computerized Tomography (SPECT/CT) imaging, standardised uptake value (SUV) quantification is being used more and more to evaluate bone metabolism. However, consistency in clinical interpretation is limited by differences in SUV values between anatomical sites and normalisation techniques. In order to improve reproducibility, this study will quantify SUV in normal vertebrae and pelvis using SPECT/CT, identify factors that influence variability, and recommend standardized measurement locations. Methods: A retrospective analysis was carried out utilising the SPECT/CT images of 36 adult patients who had 99mTc-MDP imaging at Hospital Pakar Universiti Sains Malaysia (HPUSM) and had normal pelvis and vertebrae. Relevant scan settings and patient data were gathered from logbooks and PACS. Using Q.Metrix software, SUVmax and SUVmean were computed and standardised by body weight (BW), lean body mass (LBM), and body surface area (BSA) from 963 normal sites. The SUV variability between skeletal areas was evaluated using the coefficient of variation (CoV). To evaluate SUV variability and its correlation to patient factors, statistical analysis was carried out using SPSS. Results: The mean ± SD for SUVmax and SUVmean were 7.082 ± 2.922 and 3.891 ± 1.352 (BW), 5.152 ± 2.135 and 2.843 ± 1.039 (LBM), and 1.803 ± 0.725 and 0.994 ± 0.354 (BSA), respectively. In general, the SUVmean had a lower coefficient of variation than the SUVmax, with the SUVmean BW and BSA having the lowest (0.29). There was no significant correlation between SUVs and patient factors (age, height and weight). The lowest CoV was shown by the T3 vertebral level (BSA SUVmax) and T5 level (BW SUVmean), which were suggested as the standard reference locations. BSA normalization showed superior consistency compared to BW and LBM. Conclusion: As a reference for SPECT/CT studies, BSA-normalized SUVmean offers the most stable measurement in normal bone. T3 and T5 are proposed as the standard reference levels for SUVmax and SUVmean, respectively, in this study. To improve generalisability and clinical value, larger cohorts and standardised cancer types are required for future studies.